Effect of Embryo Vitrification on Rabbit Foetal Placenta Proteome during Pregnancy. - Maria Desemparats Saenz-de-Juano; José Salvador Vicente; Kristin Hollung; Francisco Marco-Jiménez (PLoS ONE, 2015)
Very limited information on the post-implantatory effects of vitrification has been published till now. We observed in a previous study that the vitrification procedure for the cryopreservation of embryos introduced transcriptomic and proteomic modifications in the rabbit foetal placenta at the middle of gestation. Now, we have conducted a proteomic study to determine whether protein alterations in the foetal placenta induced by the vitrification procedure remain during pregnancy. In this study, we used 2D-DIGE and mass spectrometry (MALDI-TOF-TOF and LC-MS/MS analysis) to identify the protein changes during middle and late stages of gestation (Day 14 and Day 24, respectively) in rabbit foetal placenta. We identified 11 differentially expressed proteins at Day 14 and 13 proteins at Day 24. Data are available via ProteomeXchange with identifiers PXD001840 and PXD001836. In addition, we demonstrate the presence of three proteins, serum albumin, isocitrate dehydrogenase 1 [NADP+], and phosphoglycerate mutase 1, which were altered during pregnancy. We demonstrate the existence of changes in foetal placental protein during pregnancy induced by the vitrification procedure, which brings into question whether vitrification effects observed during foetal development could lead to physiological and metabolic disorders in adulthood. This effect, taken together with other effects reported in the literature, suggests that embryo cryopreservation is not neutral.